2022
DOI: 10.3390/ijms232213709
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic Activity, Cytotoxicity, and Antimicrobial Effects of Silver Nanoparticles Conjugated with Lincomycin or Cefazolin

Abstract: The overuse of antibiotics has led to the emergence of resistant bacteria. A good alternative is silver nanoparticles, which have antibacterial activity against Gram-negative and Gram-positive bacteria, including multidrug-resistant strains. Their combination with already known antibiotics has a synergistic effect. In this work, we studied the synthesis of conjugates of silver nanoparticles with two antibiotics, lincomycin and cefazolin. Albumin and glutathione were used as spacer shells with functional groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The hemolytic activity of SFE was further investigated. The off-fiber sheep blood (1001339-1, Hopebio) was centrifuged at 2000× g for 5 min to collect the red cells [ 45 ]. The red cells were incubated in PBS (1 mL) containing SFE at 37 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The hemolytic activity of SFE was further investigated. The off-fiber sheep blood (1001339-1, Hopebio) was centrifuged at 2000× g for 5 min to collect the red cells [ 45 ]. The red cells were incubated in PBS (1 mL) containing SFE at 37 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Few reviews and articles have demonstrated silver nanocomposites to be able to inhibit human cancer cells via different mechanisms. [9][10][11][12][13][14][15][16][17] In ref. [9] the cytotoxic activity of silver nanoparticles (<28 nm) and silver ions against T47D breast cancer cells was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Combined therapy approaches to control infections have been another attractive strategy, especially in those caused by multidrug-resistant microorganisms [34,35]. Some advantages may be associated with the use of combined therapy, such as the synergistic effect due to action on multiple targets, a broad spectrum of action, improvement in the bioavailability of one or more compounds, and reduced risk of both the toxicity and the emergence of resistance during treatment [36].…”
Section: Introductionmentioning
confidence: 99%
“…This antifungal combination aims to reduce the fungal burden on the host and the risk of treatment failure [37]. From this perspective, the combination of silver nanopar-ticles (AgNP) with different compounds, including antimicrobials, has been extensively investigated [34,35].…”
Section: Introductionmentioning
confidence: 99%